The Diversity, Distribution and Conservation of Bali’s Medinilla in Eka Karya Bali Botanical Garden - Ni Putu, Ni Putu Sri Asih; Sudirga, I Gusti Made Sudirga; I Gede, I Gede - Tirta (Forestry Department, University of Muhammadiyah Makassar, 2021)
Medinilla is a tropical forest plant that has potential as an ornamental and medicinal plant. The diversity of medinilla in Bali is poorly studied. This study aims to determine the diversity, distribution and conservation activities of Bali’s medinilla at the Eka Karya Bali Botanical Garden. An observational study, documentation and literature were used in this research. Based on this research, it is known that there are six species of medinilla in Bali such as Medinilla crassifolia (Reinw.ex Blume) Blume, Medinilla alpestris Blume, Medinilla laurifolia (Blume) Blume, Medinilla radicans (Blume) Blume, Medinilla speciosa (Reinw.ex Blume) Blume and Medinilla quadrifolia (BI.) Bakh. F. M. quadrifolia is a new distribution record for Bali. All species were discovered in the districts of Buleleng, Bangli, Gianyar, Jembrana, Karangasem and Tabanan districts. Only four species have been conserved in the Bali Botanical Gardens, according to data from the Eka Karya Bali Botanical Gardens' collection, therefore exploration and collection activities are critical. Conservation activities carried out at Eka Karya Bali Botanical Garden are collecting and data collection, maintaining and propagating species of medinilla.